If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -6 = -22 Reorder the terms: -6 + -2x = -22 Solving -6 + -2x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = -22 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = -22 + 6 -2x = -22 + 6 Combine like terms: -22 + 6 = -16 -2x = -16 Divide each side by '-2'. x = 8 Simplifying x = 8
| -78=-30+6x | | 2(2x+8)=2(3x+6) | | 33-18=3(x-2) | | 2x^4-7x^3+14x^2-28x+24=0 | | 24+5y-7=16y-10-2y | | d^2+18(d+4)=9 | | 3(2n-4)=(8n+6)+9 | | 35+11x=2x-100 | | -84=-8+2(8p-6) | | x^2=4x+12 | | x+19+4x=-41-4x-48 | | 59=-51+10x | | 36x^2-54x-360=0 | | -12x-20=-10x+100 | | 8y+3(y-5)=4(y+1)-2 | | 18.10x=63.35 | | 17-6x=9+2x | | x^3+5x^2+7x-8=0 | | 3x-3(5x+4)=-72 | | 1.6=18.10x | | 8-7(-8r-2)=-426 | | 5x-5=6x+8 | | -9y= | | 7v*2-9v= | | -6z-z=7z-7-9z | | 10x-4=x-4 | | -x+8=21 | | -15x=10 | | 5b-8(1+8b)=-126 | | 18.10x=1.1 | | 11x+72=-126 | | 4(4x+4)=6(x-2) |